Can Enhanced Awareness Change Local School Children's Knowledge of Carnivores in Northern Tanzania?. Issue 5 (2nd September 2016) - Lyamuya, Richard D.; Strande Straube, Anne Cathrine; Guttu, Ane M.; Masenga, Emmanuel H.; Mbise, Franco P.; Fyumagwa, Robert D.; Stokke, Bård G.; Jackson, Craig R.; Røskaft, Eivin
ABSTRACT: We used a four-day program with a pre-test–post-test approach on 355 selected school children to investigate the influence of a wildlife education project on the acquisition of knowledge about large carnivores in Loliondo, Tanzania. After the school program was completed, a significantly higher number of school children correctly identified six carnivore species, compared to when the same identification task was administered prior to the initiation of the school program. This increased knowledge is important for the conservation of large carnivores in general and of African wild dogs, in particular, because the post-test results showed that most school children considered wild dogs to be an important part of the ecosystem. In areas experiencing human– carnivore conflict, it is important to include conservation education programs in school curricula as early as possible to enable students to gain knowledge of large carnivores and their role in ecosystems.